Developing healthy eating promotion mass media campaigns: A qualitative study - Capitao, C (2022)
Background: Involving consumers in the development and assessment of mass media campaigns has been advocated, though research is still lacking. This study aimed to explore opinions and attitudes of citizens, health professionals, communication professionals, and digital influencers regarding the development and implementation of healthy eating promotion mass media campaigns. Methods: We conducted five semi-structured focus groups, where participants were exposed to the first nationwide mass media campaign promoting healthy eating in Portugal. Through criteria-based purposive sampling, 19 citizens, five health professionals, two communication professionals, and four digital influencers were included. Transcripts were analyzed using Charmaz's line-to-line open coding process. Results: Main identified themes were: considerations about informative-centered campaigns, health/nutritional issues to address, campaign formulation, target audiences, dissemination channels, and influencers' involvement. Participants favored campaigns focused on practical, transformative, and useful information with simple, innovative, activating, and exciting messages instead of strictly informative campaigns. Health and communication professionals mentioned the importance of adapting the message and dissemination channels to the target audience, addressing the most vulnerable and hard-to-reach individuals, and highlighted the importance of short video format. Conclusions: Active involvement of the health promotion target audience is crucial for the development and effectiveness of health campaigns. Campaigns need to convey health messages on simple though exciting communication materials, targeted to the most vulnerable subgroups, including deprived, less educated, younger, and older generations.